Embodied cognition and L2 sentence comprehension: an eye-tracking study of motor representations - Shiang, Ruei-Fang; Chern, Chiou-Lan; Chen, Hsueh-Chih (Frontiers in Human Neuroscience, 2024)
Introduction Evidence from neuroscience and behavioral research has indicated that language meaning is grounded in our motor–perceptual experiences of the world. However, the question of whether motor embodiment occurs at the sentence level in L2 (second language) comprehension has been raised. Furthermore, existing studies on motor embodiment in L2 have primarily focused on the lexical and phrasal levels, often providing conflicting and indeterminate results. Therefore, to address this gap, the present eye-tracking study aimed to explore the embodied mental representations formed during the reading comprehension of L2 action sentences. Specifically, it sought to identify the types of motor representations formed during L2 action sentence comprehension and the extent to which these representations are motor embodied. Methods A total of 56 advanced L2 learners participated in a Sentence–Picture Verification Task, during which their response times (RTs) and eye movements were recorded. Each sentence–picture pair depicted an action that either matched or mismatched the action implied by the sentence. Data analysis focused on areas of interest around the body effectors. Results and discussion RTs in the mismatch condition indicated an impeding effect. Furthermore, fixations on the body effector executing an action were longer in the mismatch condition, especially in late eye-movement measures.